Early Heparin Administration Reduces Risk for Left Atrial Thrombus Formation during Atrial Fibrillation Ablation Procedures. (2nd July 2011) - Asbach, Stefan; Biermann, Jürgen; Bode, Christoph; Faber, Thomas S.
Abstract : Objective . Despite the use of anticoagulation during left atrial (LA) ablation procedures, ischemic cerebrovascular accidents (CVAs) are recognized as a serious complication. Heparin is usually given after safe transseptal access has been obtained, resulting in a short unprotected dwell time of catheters within the LA, which may account for CVAs. We investigated the frequency of CVAs and LA thrombus formation as detected by intracardiac ultrasound (ICE) depending on the timing of heparin administration. Methods and Results . Sixty LA ablation procedures with the use of ICE were performed in 55 patients. Patients were grouped by heparin administration after (Group I, n = 13 ) and before (Group II, n = 47 ) transseptal access. Group I patients were younger (56.6 ± 13.7 versus65.9 ± 9.9 years, P = .01 ); other clinical and echocardiographic characteristics did not differ between groups. Early thrombus formation was observed in 2 (15.4%) of group I patients as compared to 0% of group II patients (P = .04 ). One CVA (2.1%) occurred in one group II patient without prior thrombus detection, and none occurred in group I patients (P = ns ). Conclusion . Early administration of heparin reduces the risk of early intracardiac thrombus formation during LA ablation procedures. This did not result in reduced rate of CVAs.